2009
DOI: 10.1007/s00239-009-9269-7
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of Intracellular Isoelectric Focusing in the Evolution of Eukaryotic Cells and Multicellular Organisms

Abstract: A new scenario of the origin of eukaryotic cell and multicellularity is presented. A concentric pH-gradient has been shown to exist in the cytosol of eukaryotic cells. The most probable source of such gradient is its self-formation in gradient of electric field between center and periphery of a cell. Theoretical analysis has shown that, for example, a cell of Saccharomyces cerevisiae has enough energy to continuously sustain such gradient of strength about 1.5 kV/cm, the value sufficient for effective isoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The characterization of mW and iP for the protein sequences translated from contigs with non-synonymous mutation showed that the mW from the mutated sequences was altered, but 250 sequences did not demonstrate any changes in iP values. Flegr [30] suggested that, since cell cytoplasm pH is stratified ranging from 6.4 to 7.2 in Eukaryotes, changes in the protein isoelectric point may directly influence the localization and reactions of proteins, and it is reasonable to assume that alterations to the global protein iP may interfere in interactions between proteins and complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of mW and iP for the protein sequences translated from contigs with non-synonymous mutation showed that the mW from the mutated sequences was altered, but 250 sequences did not demonstrate any changes in iP values. Flegr [30] suggested that, since cell cytoplasm pH is stratified ranging from 6.4 to 7.2 in Eukaryotes, changes in the protein isoelectric point may directly influence the localization and reactions of proteins, and it is reasonable to assume that alterations to the global protein iP may interfere in interactions between proteins and complexes.…”
Section: Resultsmentioning
confidence: 99%
“…It must be emphasized that the frozen plasticity theory has a much broader spectrum of evolutionary and ecological implications than has been suggested and discussed by students of particular hypotheses. In fact, the picture of evolutionary and ecological processes presented by the frozen plasticity theory differs in many respects from that provided by the current textbook theory of evolution; see Table 2 , [ 54 ] and (Flegr J.: Microevolutionary a macroevolutionary implication of Frozen plasticity theory of adaptive evolution, submitted). Most of these predictions could be tested empirically and should be analyzed in greater depth theoretically.…”
Section: Discussionmentioning
confidence: 99%
“…This result may reflect recent work that has shown that pI shows a weak correlation with subcellular localization 39. However, our method is only considering shifts between compartments and does not take into account the possible cytoplasmic pI related stratification of the eukaryotic cell 8…”
Section: Resultsmentioning
confidence: 80%
“…For example, most membrane protein pI is acidic in Escherichia coli K12 that live in the basic intestines, and basic in Helicobacter pylori that are found in the acidic stomach 5, 7. Moreover, recent work hypothesizes that the eukaryotic cell cytoplasm is pI stratified, from pH 7.2 at the nuclear membrane, to 6.4 at the cell membrane 8. This cytoplasmic pH stratification hypothesis8 suggests that observed pI changes may have an important impact on signaling, localization of the proteins and as a consequence their reactions and function within the cells of different mammals.…”
Section: Introductionmentioning
confidence: 99%